THE EFFECTIVENESS OF NURSE-DRIVEN INTERVENTIONS IN REDUCING HEALTHCARE-ASSOCIATED INFECTIONS - Omrana Musa Ali Hemili, Tahani Abdulrahman Mohammed Alsaeed, Amal Abdulrhman Alkhebri, Thani Abdulrhman Alkhebri, Shroog Abdulrhman Alkhebri, Rwaida Hamed Hassan, Safiah Ibrahim, Abeer Masfer Alqhtani, Wejdan Hamed Hassan; Monyrh Mohammed F Alharbi, Aisha Marie Alsayed, Ibrahim Mohammed Hamzi, Esam Rezgullah Megdad, Abdulrahman Yahya Sahli, Dareen Helal Aljamely, Mashael Farhan Alruwaili (Chelonian Research Foundation, 2022)
Abstract Problem and Purpose: Despite the commitment of several hospitals to implementing evidence-based strategies for the prevention of nosocomial infections, there are still existing gaps in their implementation. Catheter Associated Urinary Tract illness (CAUTI) is a frequently occurring illness that may be prevented and is acquired by patients during their hospital stay. CAUTIs may lead to adverse health outcomes including patient anguish, discomfort, pain, extended hospitalization, sepsis, and heightened expenses. The objective of this quality improvement initiative was to introduce a Nurse-Driven Protocol for adult patients with indwelling foley catheters. This protocol includes a routine order, guideline, flowchart, and algorithm, and allows for the discontinuation of foleys without requiring an order from a healthcare practitioner. Approach: A nearby medical facility introduced a Nurse-Driven Protocol to handle urine catheters. The protocol granted nurses the authority to cease the use of catheters. All adult patients who were admitted to the Intermediate Care Unit (IMCU) and received indwelling foley catheters throughout the twelve-week implementation period were included in the study. Champion leaders and registered nurses were chosen and provided with in-service instruction about the Nurse-Driven Protocol. Nurses were provided with algorithmic guidelines, posters, and infographics. Champion leaders were engaged via a combination of in-person and virtual meetings, in-services, phone calls, and email reminders. The process measurements consisted of the Device Utilization Ratio (DUR) and staff compliance. The outcome measures consisted of data collected before and after the occurrence of CAUTIs, as well as the number of CAUTIs per 1,000 catheter days. Chart audit instruments were used, and data were gathered every two weeks. CAUTI rates were obtained before and after deployment. A run chart was used to present the data. Outcome: The staff training about the procedure was deemed effective with a success rate of 92%. Following the 12-week implementation period, the DUR (Drug Utilization Review) reduced to 19.2%, compared to the baseline DUR of 31%. Similarly, the incidence of Catheter-Associated Urinary Tract Infections (CAUTI) was successfully decreased to nil, compared to a baseline rate of 4. The compliance rate of the nursing personnel was 92%. Findings: The implementation period resulted in decreased rates of DUR (device utilization ratio) and CAUTI (catheter-associated urinary tract infection) in the IMCU (intermediate care unit). The Nurse-Driven Protocol proved to be a successful intervention in decreasing rates of Drug Utilization Review (DUR) and Catheter-Associated Urinary Tract Infection (CAUTI). One potential future use for this approach is to put it in the organization's process manual in order to enhance patient outcomes. Term: Catheter-associated urinary tract infections (CAUTI), nurse-driven protocol, preventing, controlling, Catheter-Related Infections, Enhancement of Quality